Schedule management for planned maintenance stops in ships: single case study in the ship industry - Azevedo, Fernando Martins de; Gonçales Filho, Manoel (Brazilian Journal of Production Engineering, 2023)
The research aimed to identify how to increase the efficiency of preventive maintenance stops in vessels through subjective proposals for improvement, based on literature and practical results. The study was based on the PMBOK 7th edition's domains of project performance and literature review. The research results were organized into eight categories: Stakeholders, Team, Development Approach and Life Cycle, Planning, Project Work, Delivery, Measurement, and Uncertainty. The findings showed that the company adopts a distributed leadership and management model that involves the team and stakeholders in the optimization process. The project's success was attributed to good governance, clear communication, and transparency, which resulted in personal and professional growth, improved team morale, and increased efficiency. The study also showed that the company used a predictive approach to the project, resulting in a more rigid and inflexible initial schedule. However, the team's experience and knowledge, coupled with good governance, allowed for successful implementation. Overall, the study provides insights into the importance of team collaboration, clear communication, and good governance in project management.
Keywords: Project Management; Preventive Maintenance; Schedule Management; Naval Maintenance